Komputerisasi Sistem Informasi Keanggotaan DPC PORMIKI Solo (SIKPOSO) Berbasis Android - Resia Perwirani; Andi Yulianto (Jurnal Infokes, 2021)
The Solo branch of the Indonesian Association of Medical Recorders and Health Information Professionals (PORMIKI) serves various kinds of correspondence requests from members. Services that are done manually cause the service to be slow. With a well-developed information system, it is hoped that the membership service process will be faster and easier. PORMIKI Solo Membership Information System (SIKPOSO), is an information system in the form of a mobile application with the Android operating system. The form of the mobile application was chosen considering the ease of access for members of PORMIKI (Indonesian Association of Medical Recorders and Health Information Professionals). The design of SIKPOSO includes the preparation of Flowcharts, Use Case Diagrams, Entity Relationship Diagrams, Data Flow Diagrams, Activity Diagrams, Wireframes, and User Interfaces as a reference for developing membership systems that currently do not exist. The method used in the development of this system is the Prototyping method. SIKPOSO is designed to provide 6 service menus, as Request for recommendation of Practice License (SIK), Request for Membership Mutation Letter, Virtual Member Card (KTA), Membership Information, Annual Fee Information and Event Information. Evaluation of the SIKPOSO design was carried out using the SUS (System Usability Scale) questionnaire, getting the final score of 77 indicating that SIKPOSO is on a B grade, have a good rating and can be accepted by user for further development.